Using Informal Assessments in Project-Based Learning to Motivate Students to Speak Up: A Classroom Action Research Learned from ESP Courses - Handoyo, Futuh; Agustina, Lia; R, Setiawan; Laaribi, Manal; Chuyen, Nguyen Thi Hong (Universitas Pendidikan Mandalika, 2024)
An assessment is a way of gathering and discussing data from various sources to gain an understanding of what a student knows, understands, and is able to do with their knowledge resulting from their education to improve their future learning. The purposes of this study were to see the motivation of students to learn the English project suggested in the ESP Course, Â Business Meetings Project, and also measured the student's success in language skills, especially oral communication skills.The study was conducted Â using an action research method where a questionnaire, students' achievements, and classroom activities were taken as the data. The questionnaire was scored using the Likert scale rating. Students will respond to this scale by rating the motivation factor on a scale. The researchers employed a pre- and post-test to determine how much the students' abilities had improved. The pre-test and post-test mean scores were compared and computed by the researcher using the T-test technique. The participants were 26 students from the Accounting Department of the State Polytechnic Of Malang. The outcome of this study was the successful implementation of the model. The T-test for the first project showed 62,30, the second project had 74,69, and the third project had 79,30.